An overview on the therapeutic potential and anticancer mechanism of Monacolin K / Lovastatin - Monu Monu; Krishan D Sehrawat; Anoop Singh; Gaurav Chaudhary; Deepak Bamal; Anita R Sehrawat (Elsevier, 2022)
Rising pollution levels, altered lifestyles, and poor diets are contributing to a dramatic increase in the prevalence of cancer worldwide. When it comes to threats to human health, cancer is among the top concerns. For decades, natural products, particularly secondary metabolites derived from fungi, have been used to treat a range of chronic diseases, including cancer. Red yeast rice (RYR), is a type of traditional Chinese medicine that has been utilized throughout Asia for about one thousand years, both in culinary and curative contexts. The principal active compound in RYR is Monacolin K, a secondary fungal metabolite that is a leading drug for lowering blood lipid levels and treating hypercholesterolemia. Monacolin K also prevents gastric cancer, colon cancer, breast cancer, acute myeloid leukemia, and nervous system disorder like depression, Parkinson's disease, and schizophrenia. This review article explains the biosynthetic pathway as well as the mechanism of action of lovastatin in reducing blood cholesterol levels, cancer, neurological disorders, and antifungal activities. It also highlights the futuristic role of lovastatin in the food and drug industry.